Pembuatan Virgin Coconut Oil (VCO) Dengan Metode Enzimatis Dan Fermentasi - Teja Dwi Dwi Sutanto; Devi Ratnawati; Agus Martono HP (Indonesian Journal of Community Empowerment and Service (ICOMES), 2021)
Virgin coconut oil (VCO) is coconut oil that contains medium chain fatty acids (MCFA) which are easily broken down by the body in very high amounts. Besides that, VCO also has very high antioxidant content such as tocopherol and beta-carotene. This PPM activity aims to provide VCO Making Training with the Enzymatic Method with pineapple fruit extract and fermentation with baker's yeast in the community of RT 12 RW 03 Pematang Governor Village, Muara Bangkahulu District, Bengkulu City. The activity began with a lecture followed by a discussion and practice of making VCO with enzymatic and fermentation methods. The results of observations in the field indicate that the target community of this PPM activity is very enthusiastic to take part in this activity because they feel they have gained additional new knowledge about how to make VCO which can complement their knowledge of the known VCO making technique, namely the fishing method. With the knowledge of making VCO taught in this activity, the target community will be able to have alternative methods for making VCO other than what has been known so far with easily obtained equipment. Keywords:   VCO; MCFA; antivirus; enzymatic; Fermentation